DEVELOPMENT OF ANDROID-BASED SCRAPBOOK DIGITAL MEDIA MATERIAL ON THE RELATIONSHIP BETWEEN THE IMAGE OF THE STATE EMBLEM AND THE PRECEPTS OF PANCASILA STATE JUNIOR HIGH SCHOOL 1 FIFTY - Ade Chia Syafira; Syarbaini Saleh (STKIP Singkawang, 2024)
Currently, teachers only focus on using package books in teaching in the classroom. Without the sophistication of technology that is not combined with teaching media, it will form students who do not show enthusiasm and do not have character in the learning process. Therefore, researchers are interested in making android-based scrapbooks. This study aims to determine the feasibility, practicality and effectiveness of the scrapbook. This research is a research and development or R&D with a model of 4-D to 3-D. The result of this research is that the value of Aiken's V calculation on the validation data of material experts is 0.903 and media experts of 0.8 is classified as suitable for use. Then the results of V Aiken's calculation, student response data of 0.932 and teacher response data of 0.894 are classified as very practical to use during learning. Meanwhile, the calculation of the t-Paired test on the pretest and post-test results obtained a t-count value = 6.18 and a t-table value = 2.039. Since t-count > t-table, it has a